The Mangaroon Orogeny: Synchronous c. 1.7 Ga magmatism and low-P, high-T metamorphism in the West Australian Craton - Piechocka, Agnieszka; Zi, Jianwei; Gregory, Courtney; Sheppard, Steve; Korhonen, F.J.; Fitzsimons, Ian; Johnson, Tim; Rasmussen, Birger (ELSEVIER, 2019)
The Capricorn Orogen records nearly one billion years of intraplate orogenesis within the West Australian Craton, although the processes responsible for this protracted, punctuated reworking remain unclear. Of the major tectonic events that affected the region, the 1680–1620 Ma Mangaroon Orogeny is one of the least-well understood, mainly due to a lack of direct ages for metamorphism, an absence of pressure (P)–temperature (T) constraints, and uncertainty regarding the duration of granitic magmatism that is spatially and, possibly, temporally associated with deformation. In this study we define the P–T–time (t) conditions associated with the Mangaroon Orogeny based on in situ SHRIMP U–Pb monazite and xenotime geochronology and calculated P–T pseudosections. Data from a pelitic migmatite constrain the timing of low–P, high–T metamorphism to 1691 ± 7 Ma at conditions of 665–755 °C and 2.7–4.3 kbar (~175–240 °C/kbar). Data from a garnet-bearing sillimanite–biotite pelitic gneiss suggests higher pressure during the clockwise prograde history at one locality. Furthermore, the onset of the metamorphism coincides with the oldest granites in the region (1695 ± 9 Ma), which constrain the onset of the Mangaroon Orogeny. Our results also show that deposition and burial of the precursor sediments occurred, at most, c. 70 million years before the onset of partial melting at c. 1695 Ma. Therefore, there was no long incubation period before the onset of orogenesis. We conclude that, unlike many of the Proterozoic orogenic events in Australia, the c. 1.7 Ga low-P, high-T metamorphism recorded in the upper crust in the Capricorn Orogen cannot be explained by a thermal lid model, but rather was synchronous with granitic magmatism.